1998
DOI: 10.1046/j.1471-4159.1998.70030899.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GABA Receptor ρ Subunits in Rat Brain

Abstract: The GABA receptor ρ1, ρ2, and ρ3 subunits are expressed in the retina where they form bicuculline‐insensitive GABAC receptors. We used northern blot, in situ hybridization, and RT‐PCR analysis to study the expression of ρ subunits in rat brains. In situ hybridization allowed us to detect ρ‐subunit expression in the superficial gray layer of the superior colliculus and in the cerebellar Purkinje cells. RT‐PCR experiments indicated that (a) in retina and in domains that may contain functional GABAC receptors, ρ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
121
1
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 32 publications
8
121
1
3
Order By: Relevance
“…Binding of the ligand GABA opens the integral chloride ion channel, driving the membrane potential toward the chloride equilibrium potential and thus reducing sensitivity to excitatory neurotransmitters. The rarer GABA C receptor, another member of the inotropic GABA receptor family, is a homomeric assembly of 1 subunits (Shimada et al, 1992;Amin and Weiss, 1996); a search for endogenous mRNA using reverse transcription-PCR found 1 only in bipolar cells of the retina (Boue-Grabot et al, 1998), although other types of subunits are found elsewhere in the CNS (Wang et al, 1994;Enz and Cutting, 1999). Recent evidence that 1 subunits do not coimmunoprecipitate in vitro with ␣ 1 , ␣ 5 , or ␤ 1 subunits of GABA A suggests that 1 subunits do not associate with GABA A subunits to form receptors (Hackam et al, 1998).…”
Section: Abstract: Gaba C Receptors; Hippocampal Neurons; Adenovirusmentioning
confidence: 99%
“…Binding of the ligand GABA opens the integral chloride ion channel, driving the membrane potential toward the chloride equilibrium potential and thus reducing sensitivity to excitatory neurotransmitters. The rarer GABA C receptor, another member of the inotropic GABA receptor family, is a homomeric assembly of 1 subunits (Shimada et al, 1992;Amin and Weiss, 1996); a search for endogenous mRNA using reverse transcription-PCR found 1 only in bipolar cells of the retina (Boue-Grabot et al, 1998), although other types of subunits are found elsewhere in the CNS (Wang et al, 1994;Enz and Cutting, 1999). Recent evidence that 1 subunits do not coimmunoprecipitate in vitro with ␣ 1 , ␣ 5 , or ␤ 1 subunits of GABA A suggests that 1 subunits do not associate with GABA A subunits to form receptors (Hackam et al, 1998).…”
Section: Abstract: Gaba C Receptors; Hippocampal Neurons; Adenovirusmentioning
confidence: 99%
“…Recent data suggest that a 1 subunit could co-assemble with a GABA A subunit (5,6). Neuronal ATP and GABA C ionotropic receptors are involved in fast excitatory and inhibitory synaptic transmission, respectively, and display overlapping distribution in many regions of the nervous system, including DRG, dorsal horn of the spinal cord (7,8), retina (9 -13), hippocampus (14 -15), cerebellum (14,16), and anterior pituitary (17,18).…”
mentioning
confidence: 99%
“…Because P2X and 1/GABA receptors are co-expressed in the central nervous system (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), we investigated potential molecular and functional interactions between these two types of transmitter-gated channels in heterologous expression systems. We report here an intracellular inhibitory cross-talk between P2X 2 and GABA C 1 receptors.…”
mentioning
confidence: 99%
“…Besides being expressed in the retina, GABA C receptor ρ subunits were also found in other brain regions such as the hippocampus, cerebellum and the superior colliculus, as well as in the spinal cord [33][34][35][36]. Furthermore, ρ subunits were detected in secretory cells of the pituitary, in neurons of the gastrointestinal tract and in a neuroendocrine tumour cell line of the gut [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%